Predictor of Outcome Among Patients with Infertility Undergoing In-Vitro fertilization /Intracytoplasmic Sperm Insemination - Bhusal, Miluna; Subedi, Shanti; Sah, Rupam (Journal of Nobel Medical College, 2025)
Background: Infertility is a prevalent global health concern arising from diverse etiologies, including hormonal imbalances, reproductive system disorders, lifestyle factors, genetic abnormalities, and age-related declines in reproductive capacity. In vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) remain cornerstone therapeutic interventions for couples experiencing reproductive difficulties.Materials and Methods: A two years cross-sectional study was conducted to evaluate the underlying causes of infertility and to analyze treatment outcomes including success rates, pregnancy outcomes, and associated clinical factors among patients undergoing in vitro fertilization and intracytoplasmic sperm injection at the Nobel IVF Centre.Results: The study enrolled 126 patients, comprising 77 in the IVF group and 49 in the ICSI group. The mean (SD) age of participants was 33.45 ± 6.01 years, and the median (IQR) age was 34 (29–38) years. Patients were categorized according to the underlying cause of infertility, including tubal factor infertility, diminished ovarian reserve based on Anti-Müllerian Hormone (AMH) levels, polycystic ovary syndrome (PCOS), oligospermia, asthenospermia, unexplained infertility, and combined etiologies. Pregnancy-related outcomes, including implantation rates and neonatal results, were systematically documented.Conclusion: Higher pregnancy success rates were significantly associated with younger maternal age (